Aspek Komunikasi Dalam Kebijakan Izin Usaha Mikro Dan Kecil Di Kecamatan Pahandut Kota Palangka Raya - Muhammad Riban Satia; Risma Wati (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2019)
Implementation of micro and Small Business license (IUMK) in Pahandut Sub-district of Palangka Raya has been running since the year 2015. To facilitate the community to obtain this micro and Small business license, the government made a policy that the community can take care of in the district office where the business is located. And also to facilitate the licensing process, by means of management free micro and Small business license. This micro and Small business license policy aim to facilitate the public in obtaining their business legality and easy access to capital. Therefore, the purpose of this research is to know how its implementation is the communication aspects in the policy of micro and small business licenses in the district Pahandut. For the theory of communication, the theory is derived from the opinions of some experts, among them the theory of Kathleen K. Reardon. While the indicator used to determine the success of the policy using the approach expressed by George C. Edward III, among others is the aspect of communication. The research method used is qualitative descriptive. While the data collection methods use observation, interviews, and documentation. Data analysis techniques using models submitted by Miles and Huberman, consisting of data reduction, data display (data presentation), and conclusion drawing/verification (withdrawal of conclusions/verifications). The results revealed that the implementation process of micro and small business permit policy in the district Pahandut Palangka Raya city goes well but less maximum. This is because there are micro and small businesses who do not have the license and insufficient resources and some actors who still do not understand the flow of micro and small business licenses.